(untitled) (Práxis Educativa, 2021)
This is a study on the humanization processes present in the documents that guide the curricula of the courses, specifically the course of Pedagogy, in Brazil. The main purpose was to understand the ways in which the construction of this concept was guided in these documents. The Freirean thinking is central to the discussions brought up as it is understood that it may assist in the construction of a new pedagogical paradigm, based on the principle of training for humanization. The study was guided by a documentary research, and the data were analyzed according to a qualitative perspective. As a result, discussions about teacher training in connection with legal documents are developed. Reflections are conducted with the aim of joining legislation, teachers and researchers in a humanized way. Keywords: Humanization. Pedagogy. Official documents.